Demand Growth versus Market Share Gains : Decomposing World Manufacturing Import Growth - Aksoy, M. Ataman; Ng, Francis (World Bank, Washington, DC, 2013)
This paper decomposes manufacturing import growth rates in a selected set of large industrial and developing countries (five industrial and eight developing) and measures the relative contributions of domestic demand and market share changes for two separate periods 1991/92 - 2001/02 and 2001/02 - 2007/08. It also shows the shares of imports both from the rest of the world and from developing countries for aggregate and three-digit manufacturing sectors. Import growth is much higher during the 2000s driven by higher demand growth rates. While market share changes explain most of the growth during the 1990s, its contribution is relatively smaller during the 2000s. Imports from developing countries have grown much faster both in industrial and developing country markets driven primarily by market share changes. However, more than half of market share gains by developing countries are caused by the exports of China, which accounts for more than 70 percent of market share gains of developing countries in the sample countries during the 2000s. Despite rapid growth, developing countries' share in the gross absorption of the sample countries is still low and can expand substantially even if demand growth is much lower in the near future.